A comparative study of the evolution of vulnerabilities in IT systems and its relation to the new concept of cloud computing - Kouatli, Issam (2014)
Purpose - The purpose of this paper is to classify and categorize the vulnerability types emerged with time as information technology (IT) systems evolved. This comparative study aims to compare the seriousness of the old well-known vulnerabilities that may still exist with lower possibility of happening with that of new technologies like cloud computing with Mobility access. Cloud computing is a new structure of IT that is becoming the main part of the new model of business environment. However, issues regarding such new hype of technology do not come without obstacles. These issues have to be addressed before full acceptability of cloud services in a globalized business environment. Businesses need to be aware of issues of concerns before joining the cloud services. This paper also highlights these issues and shows the comparison table to help businesses with appropriate decision-making when joining the cloud. Design/methodology/approach – A historical review of emerged vulnerabilities as IT systems evolved was conducted, then these vulnerabilities were categorized into eight different categories, each of which composed of multiple vulnerability types. Simple scoring techniques were used to build a “risk” analysis table where each vulnerability type was given a score based on availability of matured solution and the likeliness of happening, then in case of vulnerability type, another score was used to derive the impact of such vulnerability. The resulted weighted score can be derived from the multiplication of likeliness to happen score with that of its impact in case it did happen. Percentage of seriousness represented by the percentage of the derived weighted score of each of the vulnerabilities can then be concluded. Similar table was developed for issues related to cloud computing environment in specific. Findings – After surveying the historical background of IT systems and emerged vulnerabilities as well as reviewing the common malicious types of system vulnerabilities, this paper identifies 22 different types of vulnerability categorized in eight different categories. This comparative study explores amount of possible vulnerabilities in new technology like cloud computing services. Specific issues for cloud computing were also explored and a similar comparative study was developed on these issues. The result of the comparative study between all types of vulnerabilities since the start of IT system development till today’s technology of cloud computing, shows that the highest percentage vulnerability category was the one related to mobility access as mobile applications/systems are relatively newly emerged and do not have a matured security solution(s). Practical implications – Learning from history, one can conclude the current risk factor in dealing with new technology like cloud computing. Businesses can realize that decision to join the cloud requires thinking about the issues mentioned in this paper and identifying the most vulnerability types to try to avoid them. Originality/value – A new comparative study and new classification of vulnerabilities demonstrated with risk analysis using simple scoring technique.